EDUKASI DAN SOSIALISASI K3 DI BAWASLU KABUPATEN KARAWANG - Muhidin, Muhidin; Darmawan, Wendi; Yuliana, Chaerani Tri; Jumaedi, Jumaedi; Anggara, Ikbal; Widhiantika, Wieke (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2023)
The implementation of Occupational Health and Safety (OHS) in office environments plays an essential role in improving employee health and safety standards. The Electoral Supervisory Body (Bawaslu) in Karawang Regency, responsible for overseeing elections, faces challenges related to workplace risks, including musculoskeletal disorders, work-related stress, and fatigue due to high workloads. This community service program aims to increase employees' understanding and compliance with OHS procedures through education and awareness programs, including ergonomics training, stress management, use of Personal Protective Equipment (PPE), and emergency response simulations. The program results show a significant improvement in OHS awareness from 40% to 80%, and compliance with OHS procedures from 35% to 75%. Additionally, cases of musculoskeletal disorders and work fatigue have decreased by 30%. The implementation of this program demonstrates that comprehensive OHS education and awareness initiatives are effective in reducing health and safety risks in the workplace, while also fostering a sustainable safety culture. Thus, Bawaslu Karawang is expected to continue this initiative as a means of improving employee well-being in a sustainable manner